Investigation of Innovation in Wine Industry via Meta-Analysis - Ali Dogru; Joseph Peyrefitte (Wine Business Journal, 2022)
This study provides a systematic review of 76 relevant wine business studies published in the last 30 years. Our meta-analysis investigates six commonly used variables to explain wine innovation: absorptive capacity, technology adoption, sustainable practices, export orientation, firm size, and firm age. We also investigate the association between innovation and financial performance, using the reported effect sizes in the literature. Our meta-analysis reveals that absorptive capacity, technology adoption, sustainable practices, export orientation, and firm size positively correlate with innovation efforts, and innovation is positively associated with financial performance. However, we find no correlation between firm age and innovation. In addition to the meta-analysis, we apply basic text analytics and narrative review methodologies to identify a taxonomy of wine industry innovation according to four types of innovation. Based on our systematic literature review results, we make a series of managerial and policy recommendations for wine firms. Finally, we identify gaps in the literature and suggest future research directions.